La prueba testimonial no garantiza la veracidad de la posesión material objeto principal del juicio de prescripción extraordinaria adquisitiva de dominio - Tituaña Saragozin, Esperanza Del Consuelo (2014)
The Constitution of the Republic of Ecuador in Article 82 provides: "The right to legal certainty is based on respect for the Constitution and the existence of previous, clear, public and applied by the competent authorities legal standards." Article 121 of the Code of Civil Procedure, says "Evidence -. Testing involves confession from public or private documents, statements of witnesses, judicial inspection and opinions of experts or interpreters" Witnesses at trial Prescription Extraordinary purchasing domain may be encouraged to declare in favor of the plaintiff, for a friendly relationship, an economic incentive or animosity who owns the property, making the testimonial evidence unsuitable resources because people who come to testify as witnesses do not know the real facts, and yet the trial judge's houses and sentencing on the basis of the testimony given by these people, causing injury to the property owner and even deceiving those who administer justice. By eliminating the testimony in the Ordinary Extraordinary Trial Prescription Domain purchasing is intended to make the judge when sentencing successful do so based on the documentary evidence and the Judicial Inspection, applying sound judgment and in most cases, people will pay their testimonies do incentivized financially or emotionally, for friendship or cronyism, without knowing the real facts. Cases are known that some judges, building on these false witness evidence have rendered judgments in favor of the players, granting the Special Domain adverse possession, which violates the Right to Legal Certainty enshrined in the Constitution of the Republic of Ecuador, Supreme standard. Through the present work is to analyze and substantiate the need to amend Article 121 of the Code of Civil Procedure, eliminating the testimony in the trial of extraordinary acquisitive prescription domain because practice generates costs for the state and its outcome does not guarantee the possession main subject of that item trial.